Thermophysical Property Measurements of Refractory Oxide Melts With an Electrostatic Levitation Furnace in the International Space Station - Ishikawa, Takehiko; Paradis, Paul-François; Koyama, Chihiro (Frontiers in Materials, 2022)
Due to their high melting temperatures and risk of contamination from the crucibles, molten oxides whose melting temperatures are above 2000 ℃ can hardly be processed using conventional methods, explaining that their thermophysical properties are very scarce. Containerless methods with gas flows have been developed and several thermophysical properties such as density, surface tension, and viscosity have been reported. However, the gas flow has detrimental side effects such as deformation of the sample and induction of internal flow in the molten sample, which affect the accuracy of the measurements. The electrostatic levitation furnace onboard the International Space Station (ISS-ELF), which utilizes Coulomb force to levitate and melt samples in microgravity, has several advantages for thermophysical property measurements of refractory oxide melts. Levitation without a gas flow coupled to a reduced gravity environment minimizes the required levitation (positioning) force and reduces deformation as well as internal flow. This report briefly introduces the ISS-ELF facility and the thermophysical property measurement methods. The measured density, surface tension, and viscosity of molten Al2O3 are then presented and compared with the ones obtained by other methods. Finally, the measured data of refractory oxides whose melting temperatures are above 2400 ℃ are summarized.